Views from Geneva. (2021) - Robson, Verity
Abstract : Seen from here on the factory floors of the many international organizations based in Geneva, lockdown has had significant consequences in both the governance meetings and negotiations in which states engage, most notably in respect of the politics that influence our lawmaking, the participation in our meetings and negotiations, and the personal relationships between diplomats, which are essential to successful multilateralism.